Brönsted Acidic Ionic Liquids Catalysed Sequential Michael‐Like Addition of Indole with Chalcones via Claisen‐Schmidt Condensation. Issue 10 (11th March 2020) - Das, Sukanya; Porashar, Bikoshita; Saikia, Susmita; Borah, Ruli
Abstract: A sequential acidic ionic liquid catalyzed one pot approach was conducted for preparation of 3‐substituted indoles starting from in situ generated chalcones involving Claisen‐Schmidt condensation of substituted aromatic aldehydes with acetophenone followed by Michael‐like addition of indoles to these chalcones under solvent‐free thermal reactions. For this purpose, some new and some reported Brönsted acidic ionic liquids, 2‐alkyl‐1, 3‐disulfoimidazolium carboxylate [RDSIM][X] (where R=Me & Et and X=CH3 COO −, CCl3 COO −, CF3 COO − ), were analyzed to compare their Brönsted acidic strength and thermal stabilities. From this investigation, 2‐methyl‐1, 3‐disulfoimidazolium trifluoroacetate [MDSIM][CF3 COO] and 2‐ethyl‐1, 3‐disulfoimidazolium trifluoroacetate [EDSIM][CF3 COO] were determined as efficient ionic liquid catalysts for study of the two‐step one pot synthesis of 3‐substituted indoles. Abstract : The present work highlights on the one pot sequential synthesis of 3‐substituted indoles via in situ generated chalcones as precursors. The reactions were catalyzed by –SO3 H functionalized imidazolium based ionic liquid catalysts [RDSIM][X] (where R=CH3, C2 H5 and X=CF3 COO −, CCl3 COO − and CH3 COO − ).Our strategy for the synthesis of 3‐substituted indole derivatives using metal free, ligand free and solvent free conditions, coupled with the easy recycling of catalyst, isolation of products and wide functional group tolerance makes this procedure very effective and environmentally benign.